Revision of Vitruvius (Hemiptera: Heteroptera: Pentatomidae) with the description of a new species from Cambodia and Thailand - Roca-Cusachs, Marcos; Rider, David A.; Kment, Petr; Jung, Sunghoon (Zootaxa, 2024)
The monotypic Oriental genus Vitruvius Distant, 1901 (Hemiptera: Heteroptera: Pentatomidae: Pentatominae), having an intricate and confusing taxonomic history, is revised. A new species, Vitruvius dobby Roca-Cusachs, Rider & Kment new species, is described from Cambodia and Thailand. Notes on the hypothesized classification of the genus based on both biology and morphology are presented, but its systematic placement is left unresolved. The morphological characteristics of the genus are redescribed. Habitus photographs of the type specimen of V. insignis Distant, 1901 and its labels, and photographs of both the species are provided.